Leveraging Technology-Mediated Adult and Distance Learning for Economic Growth in Africa# - Oduaran, Akpovire (Journal of Reviews on Global Economics, 2018)
Following the rudiments of contextual analysis, and based on theoretical and philosophical analyses, this paper explores how technology mediated adult and distance learning might contribute to the economic growth of Africa, all things remaining equal. It proceeds from the perspective of analysing the related contextual situations of selected countries in Africa through the brief review of Africa’s technology readiness, and posited that the possible gains that could be made from the application of adult and distance learning are tacitly located in somewhat perfect management of systems and sub-systems in education and the economy. Based on this analysis, it was proposed that whatever might be the state of Internet and technology readiness Africa has achieved, the successful creation of the nexus for economic growth is circumscribed unless the continent’s political stability is assured now and in the future.